Evaluation of the Impact of Training and Counseling on Improving the Quality of Human Resources in the Agribusiness Sector in Sumenep Regency - Fatmawati; Purwati Ratna Wahyuni; Ribut Santosa; Amir Hamzah (Jurnal Agricultural Science, 2024)
This study aims to evaluate the impact of training and extension services on improving the quality of human resources in the agribusiness sector in Sumenep Regency. Using both quantitative and qualitative approaches, we conducted surveys with farmers who participated in the training and extension programs and performed statistical data analysis to assess their influence on agricultural knowledge, skills, and practices. The survey results indicate that most respondents reported increased knowledge about cultivation techniques, fertilizer use, and post-harvest management after attending the training. Additionally, there was a significant increase in agricultural productivity and the adoption of new technologies among the farmers who participated in the program. Statistical data analysis shows a significant relationship between participation in training and increased agricultural productivity (p < 0.05). However, challenges such as limited access to information and resources still need to be addressed in the program's implementation. These findings suggest that training and extension programs are effective in enhancing the quality of human resources in the agribusiness sector, but improvements in accessibility and program continuity are necessary to achieve more optimal results.